Assessment of Anti-Streptokinase Antibody Levels in Human Sera Using a Microradioimmunoassay Procedure - Moran, D M; Standring, R; Lavender, E A; Harris, G S (Thrombosis and Haemostasis, 1984)
A high capacity, quantitative radioimmunoassay procedure has been developed to measure IgG antibodies to streptokinase (SK) in human serum. Results showed that the use of low concentrations of 125I-SK (100 ng/ml) and ambient temperature incubation conditions minimised degradation of the target labelled antigen and afforded antibody binding values which could be confidently related to the native intact SK protein. SK-complexed to plasminogen was also shown to retain the equivalent antigenic activity of native SK. Comparison of the absolute anti-SK levels with streptokinase resistance titres demonstrated that the two measurements of antibody correlated statistically but afforded quantitatively poor agreements. A survey of IgG levels to SK in sera from 93 normal healthy volunteers showed that all individuals displayed readily measurable anti-SK antibodies, with some 80% having IgG concentration capable of binding in excess of 1 μg SK per ml serum.
Keywords: Anti-streptokinase antibodies; Streptokinase antigenicity; Streptokinase fragmentation; Streptokinase complexes; plasminogen complexes